Реакція світової громадськості на порушення прав людини в УРСР (1976—1985 рр.) - Сімків, О. (Український визвольний рух, 2013)
У статті розглянуто зусилля української громадськості у демократичних країнах для привернення уваги держав-учасниць Гельсінкської наради з питань безпеки і співробітництва в Європі на порушення прав людини в СРСР. Простежено реакцію урядів демократичних країн та міжнародних правозахисних організацій на арешти членів УГГ. The article is devoted to the eff orts by the Ukrainian communities in democratic countries to attract the attention of member states of the Helsinki Conference on Security and Cooperation in Europe to violations of human rights happening in the Ukrainian SSR. The reaction of democratic countries’ governments and international human rights organizations to the fact of the Ukrainian Helsinki Group members’ arrests is traced.